(3JQHjI GdehGWfI Hjf GdfXQjI hGdJWHjb (B/s - (3Wg, CeGfj eMeOs; (3eQRhb, aGQhb LYaQ YHO GdMcje,s 1977- ((3GdbGgQI (B:s (3ecJHI GdCfLdh GdeUQjI,s, 2013)
(3dbO CUHMJ JQHjI GdehGWfI ef GdbVGjG GdJj JaQV faSgG HbhI YfO eYGdLI Ci HYO ef CHYGO GdJfejI GdHTQjI(B. (3hGdehGWfI HeaghegG GdhGSY JYfi GdUdI Hjf GdaQO hGdOhdI GdJj jbje ajgG HTcd KGHJ, hjQJHW HgG LZQGajG hJGQjNjG hKbGajG Cge eDTQGJgG ehba GdaQO ef GMJQGe GdbGfhf hGdfXGe GdYGe, hGdehba ef VeGf GdMQjGJ GdaQOjI hGMJQGe Mbhb GdEfSGf, hGdJSGeM hbHhd GdBNQ hMQjI GdJYHjQ hZjQgG ef GdeDTQGJ GdJj JeKd Gdbje GdCSGSjI ddehGWfI, egeG GNJdaJ GdefWdbGJ GdacQjI hGdeQLYjGJ GdadSajI dgPG GdeLJeY Ch PGc (B.(3hJYO YedjI JfejI GdehGWfI hbjegG dOi GdeJYdejf fhYkG ef GdJQHjI GdhbGFjI ; EPG Ef GcSGH hGcJSGH bje GdehGWfI jYO GdQcjRI GdCSGSjI ddeTGQcI GdEjLGHjI hGdaYGdI aj GdJfejI GdGLJeGYjI, Ch GdGbJUGOjI, hGdSjGSjI, hJfejI GdEMSGS HGdhGLH fMh GdeLJeY GdeMdj hGdOhdi(B. (3hef gfG LGAJ acQI GdcJGH GdQGgf, hGdPj jSJgOa SHQ CZhGQ GdehGWfI, hcTa eG jcJfagG ef ZehV Ydi GdeSJhjjf GdfXQj hGdJWHjbi(B.s
(3HHdjhLQGajI (B: (3UaMI (B247-263.s
Keywords: (3GdehGWfIs; (3GdJQHjI GdhWfjIs